Spatiotemporal description of BTEX volatile organic compounds in a Middle Eastern megacity: Tehran Study of Exposure Prediction for Environmental Health Research (Tehran SEPEHR). (July 2017) - Amini, Heresh; Hosseini, Vahid; Schindler, Christian; Hassankhany, Hossein; Yunesian, Masud; Henderson, Sarah B.; Künzli, Nino
Abstract: The spatiotemporal variability of ambient volatile organic compounds (VOCs) in Tehran, Iran, is not well understood. Here we present the design, methods, and results of the Tehran Study of Exposure Prediction for Environmental Health Research (Tehran SEPEHR) on ambient concentrations of benzene, toluene, ethylbenzene, p -xylene, m -xylene, o -xylene (BTEX), and total BTEX. To date, this is the largest study of its kind in a low- and middle-income country and one of the largest globally. We measured BTEX concentrations at five reference sites and 174 distributed sites identified by a cluster analytic method. Samples were taken over 25 consecutive 2-weeks at five reference sites (to be used for temporal adjustments) and over three 2-week campaigns in summer, winter, and spring at 174 distributed sites. The annual median (25 th –75 th percentile) for benzene, the most carcinogenic of the BTEX species, was 7.8 (6.3–9.9) μg/m 3, and was higher than the national and European Union air quality standard of 5 μg/m 3 at approximately 90% of the measured sites. The estimated annual mean concentrations of BTEX were spatially highly correlated for all pollutants (Spearman rank coefficient 0.81–0.98). In general, concentrations and spatial variability were highest during the summer months, most likely due to fuel evaporation in hot weather. The annual median of benzene and total BTEX across the 35 sites in the Tehran regulatory monitoring network (7.7 and 56.8 μg/m 3, respectively) did a reasonable job of approximating the additional 144 city-wide sites (7.9 and 58.7 μg/m 3, respectively). The annual median concentrations of benzene and total BTEX within 300 m of gas stations were 9.1 and 67.3 μg/m 3, respectively, and were higher than sites outside this buffer. We further found that airport did not affect annual BTEX concentrations of sites within 1 km. Overall, the observed ambient concentrations of toxic VOCs are a public health concern in Tehran. Graphical abstract: Highlights: Annual mean benzene was more than standard of 5 μg/m 3 in ∼90% of 179 measured sites. Concentrations/spatial variability were highest at summer due to fuel evaporation. Annual median at 35 regulatory network sites approximated other 144 city-wide sites. The concentrations in sites within 300 m of gas stations were higher than other sites. Airport did not affect annual BTEX concentrations of sites within 1 km.